2007
DOI: 10.1074/jbc.m706991200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Accelerates the Inhibition of Human Cathepsin V by Serpins

Abstract: A balance between proteolytic activity and protease inhibition is crucial to the appropriate function of many biological processes. There is mounting evidence for the presence of both papain-like cysteine proteases and serpins with a corresponding inhibitory activity in the nucleus. Well characterized examples of cofactors fine tuning serpin activity in the extracellular milieu are known, but such modulation has not been studied for protease-serpin interactions within the cell. Accordingly, we present an inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 43 publications
(40 reference statements)
5
25
0
Order By: Relevance
“…1b, both proteins showed a mobility shift toward the positive electrode following incubation with heparin. We also examined the ability to bind DNA using agarose gel mobility shift analysis but found no binding for either serpin (data not shown), in agreement with the findings of Ong et al (21) for SCCA-1.…”
Section: Serpins Scca-1 and Scca-2 Bind The Glycosaminoglycansupporting
confidence: 77%
See 2 more Smart Citations
“…1b, both proteins showed a mobility shift toward the positive electrode following incubation with heparin. We also examined the ability to bind DNA using agarose gel mobility shift analysis but found no binding for either serpin (data not shown), in agreement with the findings of Ong et al (21) for SCCA-1.…”
Section: Serpins Scca-1 and Scca-2 Bind The Glycosaminoglycansupporting
confidence: 77%
“…This template mechanism is found for most plasma serpin enhancement by heparin, but for SCCA-1 rate enhancement in the presence of DNA, a non-templating saturation effect was seen as a result of protease binding only (21). Using a range of heparin concentrations (Fig.…”
Section: Binding Of Heparin Quenches the Intrinsic Tryptophanmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the inhibitory activity of MENT on cathepsin L, rather than DNA binding, is crucial for mediating its effect (29). DNA was reported to accelerate the rate at which MENT inhibited cathepsin V, a human ortholog of mammalian cathepsin L, up to 50-fold (50). Therefore, the possible interaction of stefin B with DNA was analyzed by gel shift assay, as described previously (50).…”
Section: Visualization Of Intracellular Met-75 Cathepsin L-stefin B Imentioning
confidence: 99%
“…Moreover, heparan sulphate has been implicated in the regulation of the conformational plasticity of a cathepsin L homologue from Trypanosoma brucei, possibly by allosteric mechanisms 19 . Similarly, DNA has been shown to augment the inhibition of cathepsin V by serpins 20 .…”
mentioning
confidence: 99%